80 Improving Documentation of DNAR Decisions on the Acute Medical Take. (16th March 2021) - Sweeney, A; Bellenberg, H; Butt, H; Badat, S; Epstein, D
Abstract: Introduction: The BMA, Resuscitation Council and Royal College of Nursing have set out clear guidelines on documentation of Resuscitation discussions and decisions.1 On the acute medical take documentation of these discussions and decisions can be unclear despite use of an electronic patient record (EPR). The aim of this audit was to improve documentation of Do Not Attempt Resuscitation (DNAR) decisions in EPR. Methods: We listed patients admitted on the medical take over 1-week, looking at resuscitation status and the documentation of the DNAR decision. We then implemented a change to the format of the EPR treatment escalation plan (TEP) form. Prior to the change the DNAR form was behind the TEP form which had to be clicked on separately and was not mandatory to complete. After the intervention the DNAR decision was placed in a box on the front page of the TEP form to ensure that it was clear and accessible. Results: Pre-intervention we reviewed 114 patients notes of which 94 were DNAR. Of these 94 only 17 (18%) had correctly documented DNAR decisions in EPR. Following the intervention we again looked at all admissions to the medical take over a 1-week period, out of 151 patients 75 were DNAR and of these 75 patients 29 had correctly documented DNAR forms. This shows an increase in the percentage of the DNAR decisions filled in from 18% to 39%. Conclusion: The results show that although there has been an improvement in the number of DNAR decisions being documented there are still a large percentage of patients who do not have this correctly documented. We are designing further interventions to ensure that the DNAR documentation is marked as a mandatory part of the TEP form as well as educating around the importance of this documentation.